Director's perspectives on the meaning and dimensions of corporate reputation - C. Reddiar; N. Kleyn; R. Abratt (South African Journal of Business Management, 2012)
The purpose of this research is to explore the perspectives of directors to determine how they define, perceive, value, build and manage corporate reputation. A qualitative research design was employed. In order to gauge director's perspectives, 12 semi-structured, in-depth interviews were conducted with the directors of a multi-national company based in South Africa. The company operates in a highly regulated and competitive industry. The findings demonstrate that corporate reputation is indeed acknowledged as a key, intangible asset. Whilst the directors did not possess clear insight into building and managing corporate reputation, several key themes emerged. We report on their perceptions of the definitions, key dimensions and value ascribed to corporate reputation. By demonstrating the value that is associated with corporate reputation and by ascertaining that directors are indeed the appropriate custodians of corporate reputation, there will be better acceptance in introducing corporate reputation as a board room agenda item, that is well understood and implemented.
Keywords: 650